Neonatal Pain, Still Searching for the Optimal Approach - Walter-Nicolet, Elizabeth; Calvel, Laurent; Gazzo, Geraldine; Poisbeau, Pierrick; Kuhn, Pierre (Current Pharmaceutical Design, 2017)
Background: although neonatal pain management has seen huge improvements in the past years, many gaps between knowledge and practice still exist. Objective: to give the reader the state of the art of actual pain management and treatment. Methods: a literature review was done on the physiopathology of pain, sex differences in the perception of pain, epidemiology, non-pharmacological treatment and developmental care approach, pharmacological treatment with pharmacokinetics and pharmacodynamics approaches. Conclusion: despite an increasing knowledge in the field of neonatal pain, many gaps and questions remain, especially relative to the lack of assessment, prevention and treatment of painful procedures, appropriate drugs and dosing to support the well-being and the brain development of this highly vulnerable population.
Keywords: physiopathology